The Influence of Employee Performance on Customer Satisfaction, Trust, and Loyalty - Abdillah, Rony (Islamicate Institute, 2024)
This article discusses about the influence of employee performance on customer satisfaction, trust, and loyalty. The findings of this study are: the reason for customers that may be more loyal to a service’s brand is the recognition of their need by the service producers or sellers. Therefore, a customer may show greater brand loyalty in order to cultivate a satisfying relationship with the seller. The research will identify perceived service quality, consumer satisfaction, and trust that affect consumer loyalty. Researcher used structural equation model with the AMOS 4.01 program to calculate the effect of each variable. A model will be developed to describe these relationships.